Self-injury and aggression in adults with tuberous sclerosis complex: Frequency, associated person characteristics, and implications for assessment. (May 2017) - Wilde, Lucy; Eden, Kate; de Vries, Petrus; Moss, Jo; Welham, Alice; Oliver, Chris
Abstract: Even though self-injury and aggression are common in tuberous sclerosis complex (TSC), understanding of these behaviours in adults with TSC and intellectual disability (ID) is limited. Little is known about their frequency in comparison to other ID-related genetic disorders or their association with other TSC-Associated Neuropsychiatric Disorders (TAND). This study determined the caregiver-reported frequency of self-injury and aggression in adults with TSC plus ID in comparison to Down syndrome (DS) and Angelman syndrome (AS), and assessed demographic and behavioural characteristics associated with the occurrence of each behaviour in TSC. Rates of self-injury and aggression in adults with TSC plus ID were 31% and 37.9% respectively. The odds of self-injury for adults with TSC were nearly twice as high as the odds for adults with DS, and the odds of aggression were over 2.5 times higher for adults with TSC than for adults with DS. When compared to adults with AS, odds of self-injury in TSC were around half those of the AS group, and odds of aggression were less than a third of those for adults with AS. These differences were not statistically significant. In adults with TSC, poorer communication and socialisation skills, gastric health problems and impulsivity were associated with self-injury; compulsive behaviour and impulsivity were associated with aggression. Caregivers and professionals should be alert to the likelihood of these behaviours in adults with TSC plus ID, and to characteristics associated with increased risk for their occurrence. We suggest assessment strategies to identify those at elevated risk. What this paper adds: This paper adds specific examination of behavioural difficulties in adults with tuberous sclerosis complex who also have intellectual disability, a population at heightened risk of adverse behavioural outcomes which has received limited focussed examination to date. Findings support existing suggestions that there is relatively high risk for both self-injury and aggression, and provide novel insight into characteristics that may be associated with the presence of these behaviours.